Sarcomatoid malignant peritoneal mesothelioma: A rare case of sarcomatoid component with monosomy 9 appeared in ascites fluid - Yuri Noda; Yuko Nakanishi; Kumi Masuda; Masaru Yamasaki (Elsevier, 2019)
Sarcomatoid mesothelioma (SM) is the rarest subtype of malignant mesothelioma (MM) with the poorest prognosis. Due to its aggressive nature, early diagnosis and treatment are required for SM, resulting in they significantly improve patient survival. Until now, effusion cytology using ancillary techniques has aided in the early diagnosis of MM, and the cytological findings of the epithelioid component of MM have been well described. However, there has been no detailed cytomorphological description of the sarcomatoid component because it seldom shed into the body cavity fluid. This is the first case report of SM in which the sarcomatoid component with monosomy 9 appeared in the ascites fluid. A 51-year-old female presented with an elastic hard, painless mass in the abdomen. She had no history of asbestos exposure. Computer tomography revealed multiple solid masses in the abdominal and pelvic cavities with ascites fluid. Clinically, ovarian cancer or peritoneal cancer were suspected, then total laparoscopic salpingo-oophorectomy and peritoneal biopsy were performed. On cytological examination of the ascites fluid, many scattered single cells and loose aggregate cells in the inflammatory background were observed. These cells had scant, or fine and wispy cytoplasm, and atypical short-spindle or round nuclei with prominent nucleoli. Microvilli were not detected. Histological examination revealed atypical spindle cell proliferation in the left ovary and peritoneal mass. Immunohistochemically, these cells were positive for mesothelial markers, calretinin and D2-40, AE1/3 and CAM5.2. Fluorescence in situ hybridization detected monosomy 9. Based on these features, sarcomatoid malignant peritoneal mesothelioma was diagnosed. For reliable diagnosis and treatment, the possibility of SM should be considered when short-spindle cells without obvious microvilli are observed in effusion. Moreover, an integral diagnosis, including the morphological features and results of ancillary tests, is required. Keywords: Cytomorphology, Fluid cytology, Immunohistochemistry, In situ hybridization (ISH), Malignant mesothelioma, Malignant peritoneal mesothelioma, Sarcomatoid malignant mesothelioma, Sarcomatoid mesothelioma